Preserved visuospatial abilities in absence of the right hemisphere: A case of cerebral hemiatrophy with minimal cognitive impairment. Issue 3 (22nd March 2022) - Kasselimis, Dimitrios S.; Tsolakopoulos, Dimitrios; Simos, Panagiotis G.; Makryllou, Irina; Velonakis, Georgios; Politis, Antonios M.; Potagas, Constantin
Abstract : Cerebral hemiatrophy is a rare neurological condition, usually resulting in severe and diffuse cognitive impairment. In this paper we present a 69‐year old woman with notable congenital hemiatrophy with strikingly preserved cognitive functions. Cognitive assessment indicated that although her executive functions were found impaired, the remaining cognitive domains were relatively unaffected. We argue that this unexpected cognitive profile may be explained by anomalous hemispheric lateralization, driven by neuroplasticity along the developmental course.